Arctic Shipping Emissions in the Changing Climate - Vihanninjoki, Vesa (Finnish Environment Institute, 2015)
Due to the Arctic climate change and the related diminishing of Arctic sea ice cover, the general conditions for Arctic shipping are changing. The retreat of Arctic sea ice opens up new routes for maritime transportation, both trans-Arctic passages and new alternatives within the Arctic region. Hence the amount of Arctic shipping is presumed to increase. Despite the observed development, the sailing conditions in the Arctic waters will remain challenging. Thus particular attention will be required also in the future with regard to crew, fleet and other infrastructural issues. In addition to other apparent challenges and risks, the increase in Arctic shipping will lead to an increased amount of emissions. The increased emissions may have considerable and unpredictable influences to the particularly sensitive Arctic environment. With regard to emission species, especially black carbon is presumed to have climatic sig-nificance within the Arctic context. Black carbon absorbs solar radiation very effectively, and when deposited to snow or sea ice cover, it may notably alter the radiative equilibrium of the Arctic region. The increased Arctic marine activities produce black carbon emissions, whose climate impacts are assessed in this report.